Fate in Thunderstorm by Cao Yu and Hippolytus by Euripides - Zhang, Jing (Studia Azjatystyczne, 2016)
Theatre, as opposed to traditional Chinese drama, was introduced to China through the first Opium War, and the establishment of Chunliushe in Japan is regarded as the birth of the real Chinese play in 1907. Hereafter, many plays were written and performed in China and were accepted as new form plays. Thunderstorm (Leiyu), Cao Yu’s first play, was published in 1934, and became the first masterpiece of modern Chinese theatre, symbolizing its becoming mature. As the playwright admitted, it was influenced by classical Greek Plays, as well as by Henrik Ibsen. This paper reflects upon the theme of fate in Thunderstorm by Cao Yu and Hippolytus by Euripides. Although Cao Yu interpreted that he was influenced by western plays consciously or unconsciously, Thunderstorm has its own Chinese roots. Similarities and differences in the themes of fate are compared by time or history; ethnic or family aspects; and the individual or feminine. The indescribable fate of the protagonists leads to the agony they suffer inside and also effects them outside because of typical social beliefs and family life; meanwhile, it helped to bring fame to the two tragedies.